The research of the world experience in the use of blockchain technologies - Abaidullin, А.А.; Sabyrzhan, A.; Ashirbekov, N.K. (BUKETOV BUSINESS REVIEW, 2024)
Object: To explore experience of using blockchain and identification of problems those hinder its development in Kazakhstan. Methods: General scientific methods employed in this study included descriptive, retrospective, system analysis, synthesis of the subject, as well as system-structural and system-functional analyses. In addition, specific methodologies such as modeling, formal logic, comparative analysis, comparative legal analysis, SWOT, and PEST analyses were utilized. Processing of the data was carried out through the EXCEL. Findings: Digital technologies are becoming the main trends. Their promotion changes life and stimulates to work on development of social, economic spheres. It is accepted that they increase the efficiency of not only personal life, but also the economy. Conclusions: The solution to the problems is possible through the harmonization of legislative standards, investments in educational programs and the involvement of international experience. The example of the eGov 3.0 initiative has shown the importance of algorithmic approaches and predictive management for optimizing the interaction between the state and society. Based on the above, blockchain acts as a strategic tool for modernizing the economy and increasing its sustain ability. The introduction of distributed ledger technologies, taking into account global experience, will allow Kazakhstan to effectively adapt to global challenges, strengthening the institutional environment and stimulating innovative development.